The Relationship Between the Beneish M-Score and the Altman Z-Score: Evidence from Energy Sector Companies in Indonesia - Agung Rachmad Prasetyo; Linda Santioso (Golden Ratio of Auditing Research, 2026)
The energy sector plays a strategic role in the Indonesian economy; however, its high exposure to commodity price volatility makes it particularly vulnerable to irregularities in financial reporting. This study examines the relationship between the Beneish M-Score and the Altman Z-Score in detecting fraudulent financial reporting among energy companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Employing a quantitative descriptive-comparative research design, this study analyzes 183 firm-year observations from 61 companies selected through purposive sampling. The analysis consists of three stages: classification based on the threshold values of each model; cross-tabulation combined with the chi-square test and Cramér's V to evaluate the consistency between the two classification models; and pooled ordinary least squares (Pooled OLS) regression with robust standard errors to examine whether financial distress influences earnings manipulation. The findings indicate that 38.80% of the observations are classified as potential manipulators according to the Beneish M-score, while 42.62% are categorized as financially distressed based on the Altman Z-score. A statistically significant association was found between the two classification models (χ² = 11.83, p = 0.003; Cramér's V = 0.254). However, the distribution exhibited an unexpected U-shaped pattern, with the highest proportion of potential manipulators observed in the safe zone (52.24%), followed by the distress zone (37.18%), and the lowest proportion in the grey zone (18.42%). Consistent with this non-monotonic relationship, neither the overall Altman Z-score nor any of its five financial ratio components had a statistically significant effect on the Beneish M-score in the linear regression model. These findings suggest that financial distress alone is insufficient to explain earnings manipulation in the energy sector and highlight the importance of monitoring financially healthy firms, particularly during commodity price booms.